Supertetragonal Phases of Perovskite Oxides: Insights from Electronic Structure Calculations. Issue 8 (5th May 2020) - Cohen, Netanela; Diéguez, Oswaldo
Abstract: We review some of the insights that electronic‐structure calculations has brought about the properties of the materials with the largest electric polarization known – supertetragonal perovskite oxides. These are materials whose structure corresponds to a perovskite that has been substantially strechted along one of its pseudocubic axes. They grow in different forms: bulk crystals (such as BiCoO3 ), epitaxial films (such as BiFeO3 ), nanowires whose inside is under negative pressure (such as PbTiO3 ), and others. Electronic structure calculations based on density‐functional theory have revealed that supertetragonality potentially exist for many perovskite oxides under the right conditions, and they have helped explain why some of those conditions are easy to reach for some of the materials of the family, but not for others. Abstract :